Znaczenie Uniwersytetu w Dorpacie dla kultury i nauki polskiej (przed 1917 r.) - Blombergowa, Maria Magdalena (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The University of Dorpat founded at the beginning of the 19th century almost at the very beginning enjoyed a high level of education. Among the teachers there were many eminent scientists of European fame. The school had the following faculties of: law, teology, medical faculty and philosophy. The last faculty included the specializations of: phisico-methematical, natural, historical-phylological and technological-economical. For many years the University as regards the organization and the character was German yet it managed to preserve its separateness even in times of increased oppression. Russian language was introduced in 1889 and the complete Russification took place in 1893. The University of Dorpat almost for the whole 19th century was one of the most liberal universities in Russia. Polish students came to Dorpat almost from the beginning of the existence of the University and they were accepted there more readily than at other Russian universities. The first Polish students came from White Russia and the region of Vilna. After the Universities of Warsaw and Vilna had been closed the Polish students came from other towns of Russia, Russian and Prussian and Austrian sectors of partitioned Poland. It is commonly thought that in 1802-1917 about 1500-2000 Polish students were studing at the Dorpat University. Majority of them achieved diplommas and university degrees. Medical studies were the most popular next came law, teology, economy, chemistry, pharmacy, phylology, physics, botany and technology. The Polish youth considered it a patriotic duty to achieve high professional qualifications and to prepare themselves for working in the future free fatherland. The large amount of golden medals for students' scientific works won by the Polish can confirm the serious approach to studies of those young people. As compared to the large number of Polish graduates and very good opinion about them few Polish students were appointed to a professorship at the University of Dorpat. The origin of Polish students and the mistrust of Russian administration prevented them from university chairs. Most of graduates finished their career as assistants or private assistants professors. To 1917 the following scientist became the professors of Polish origin: Jan Baudouin de Courtenay, Adam Zaczyński, Stanisław Czyrwiński, Tadeusz Banachiewicz and Aleksander Bylina. Polish graduates at Dorpat University were appointed to professorships at other Russia and foreign universities. Many professors and lecturers working at schools of the sovereign Poland and also many scientists of different disciplines, social workers, writers, doctors, engineers recruited from the graduates of Dorpat University. The University of Dorpat played a significant role in the development of Polish higher education and forming of Polish inteligentia.